Exploring the causal connection: insights into diabetic nephropathy and gut microbiota from whole-genome sequencing databases - Rui Lin; Rongping Chen (Renal Failure)
Over recent years, the prevalence of diabetes has been on the rise, paralleling improvements in living standards. Diabetic nephropathy (DN), a prevalent complication of diabetes, has also exhibited a growing incidence. While some clinical studies and reviews have hinted at a link between diabetic nephropathy and gut microbiota (GM), the nature of this connection, specifically its causative nature, remains uncertain. Investigating the causal relationship between diabetic nephropathy and gut microbiota holds the promise of aiding in disease screening and identifying novel biomarkers. In this study, we employed a two-sample Mendelian randomization analysis. Our dataset encompassed 4,111 DN patients from the GWAS database, juxtaposed with 308,539 members forming a control group. The aim was to pinpoint specific categories within the vast spectrum of the 211 known gut microbiota types that may have a direct causal relationship with diabetic nephropathy. Rigorous measures, including extensive heterogeneity and sensitivity analyses, were implemented to mitigate the influence of confounding variables on our experimental outcomes. Ultimately, our comprehensive analysis revealed 15 distinct categories of gut microbiota that exhibit a causal association with diabetic nephropathy. In summary, the phyla Bacteroidota and Verrucomicrobiae, the families Peptostreptococcaceae and Veillonellaceae, the genus Akkermansia, and the species Catenibacterium, Lachnoclostridium, Parasutterella, along with the orders Bacteroidales and Verrucomicrobiales, and the class Bacteroidetes were identified as correlates of increased risk for DN. Conversely, the family Victivallaceae, the species Eubacterium coprostanoligenes, and the Clostridium sensu stricto 1 group were found to be associated with a protective effect against the development of DN. These findings not only provide valuable insights but also open up novel avenues for clinical research, offering fresh directions for potential treatments.